Biology, Ecology, and Management of Eastern Grape Leafhopper (Hemiptera: Cicadellidae), a Key Pest of Vineyards in North America. (18th May 2020) - Jarrell, Kevin R; Rebek, Eric J; Wayadande, Astri C; Giles, Kristopher L
Abstract: Eastern grape leafhopper, Erythroneura comes (Say), is a key pest of grapes (Vitales: Vitaceae) in the central and northeastern United States and eastern Canada. This native insect uses its piercing-sucking mouthparts to puncture the mesophyll cells of leaves and suck out the contents, thereby reducing the quality and quantity of fruit. Eastern grape leafhopper has been reported as a vineyard pest for nearly 200 yr and is one of several Erythroneura spp. that feed on grapes in North America. Overwintered adults become active in early spring and may feed on grasses, weeds, and other plants before feeding on grapevines. Although eastern grape leafhopper has an extensive host range, it is only known to oviposit on wild and cultivated grapes. This multivoltine species can outbreak periodically, which has generated much research into improved monitoring and integrated pest management strategies employed throughout its native range. In this review, we describe the biology, life history, population dynamics, and phenology of eastern grape leafhopper and provide a historical account of monitoring and management strategies for this important vineyard pest.